ANALISIS ISI OBJEKTIVITAS BBC INDONESIA DALAM PEMBERITAAN ISU LINGKUNGAN NASIONAL VS. INTERNASIONAL - Beti Hapsarie (Fakultas Hukum Universitas Kadiri, 2021)
Abstract - This study examines the objectivity of BBC Indonesia’s coverage of the Amazon and Kalimantan forest fires. This study aims to see whether there are differences in objectivity between the coverage of International and National environmental issues published in one media, especially when it’s affiliated with international media. McQuail (2000) defines media objectivity as taking a separate and neutral position by removing the subjectivity and personal opinion of journalists on news objects or news sources. Quantitative content analysis was carried out on 30 news items collected during the July-September 2019 period and coding was carried out using 8 indicators according to the Westerstahls objectivity scheme. From the test results, it is knows that there is no difference in objectivity in the reporting of forest fires in Kalimantan and the Amazon to BBC Indonesia. the results of this test are still in line with the concept of environmental journalism, where every journalist is required to take sides and support the environment itself. However, when compared with previous studies, the test results in this study show a difference. This is because in previous research, the topics raised were related to politics, not the environment.Keywords: News Objectivity, National and International News, Environmental Journalism